Mechanical characterization of human brain tissue - Budday, Silvia; Sommer, Gerhard; Birkl, Christoph; Langkammer, Christian; Haybaeck, Johannes; Kohnert, Julius; Bauer, Melanie; Paulsen, Friedrich; Steinmann, Paul; Kuhl, Ellen; Holzapfel, Gerhard A. (Acta Biomaterialia, 2017)
Mechanics are increasingly recognized to play an important role in modulating brain form and function. Computational simulations are a powerful tool to predict the mechanical behavior of the human brain in health and disease. The success of these simulations depends critically on the underlying constitutive model and on the reliable identification of its material parameters. Thus, there is an urgent need to thor- oughly characterize the mechanical behavior of brain tissue and to identify mathematical models that cap- ture the tissue response under arbitrary loading conditions. However, most constitutive models have only been calibrated for a single loading mode. Here, we perform a sequence of multiple loading modes on the same human brain specimen – simple shear in two orthogonal directions, compression, and tension – and characterize the loading-mode specific regional and directional behavior. We complement these three indi- vidual tests by combined multiaxial compression/tension-shear tests and discuss effects of conditioning and hysteresis. To explore to which extent the macrostructural response is a result of the underlying microstructural architecture, we supplement our biomechanical tests with diffusion tensor imaging and histology. We show that the heterogeneous microstructure leads to a regional but not directional depen- dence of the mechanical properties. Our experiments confirm that human brain tissue is nonlinear and vis- coelastic, with a pronounced compression-tension asymmetry. Using our measurements, we compare the performance of five common constitutive models, neo-Hookean, Mooney-Rivlin, Demiray, Gent, and Ogden, and show that only the isotropic modified one-term Ogden model is capable of representing the hyperelastic behavior under combined shear, compression, and tension loadings: with a shear modulus of 0.4–1.4 kPa and a negative nonlinearity parameter it captures the compression-tension asymmetry and the increase in shear stress under superimposed compression but not tension. Our results demonstrate that material parameters identified for a single loading mode fail to predict the response under arbitrary loading conditions. Our systematic characterization of human brain tissue will lead to more accurate com- putational simulations, which will allow us to determine criteria for injury, to develop smart protection sys- tems, and to predict brain development and disease progression.
Keywords: Human brain; Mechanical testing; Hyperelastic modeling; Mooney Rivlin model; Ogden model